Why documentaries matter - Fraser, N (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2012)
Documentaries have for many decades inhabited the schedules of public broadcasters. They have chronicled the lives and institutions of western democracies. In the past two decades, however, documentaries have become recognised as an innovative cultural form. Instead of being exclusively funded by television channels, documentaries receive money from a number of sources, including film funds, private investors and foundations. Rather than observing, documentaries are now thought capable of changing the world. Is this what they really do? How do we define a documentary? What does it mean to be the 'author' of a film? Nick Fraser has been editor of the BBC's Storyville series since 1997; here he looks at the history of documentaries, showing how definitions of documentaries have changed – and how fragile is their funding. If we want good documentaries, he concludes, we have to find ways of encouraging their creators.